PENGARUH PEMANFAATAN DAUN UBI JALAR (Ipomea batatas L) TERHADAP PERFORMANS TERNAK KELINCI - Sampul, Meysi B.; Tulung, B.; Umboh, J.F; Moningkey, S.A.E. (Universitas Sam Ratulangi, 2018)
THE EFFECT OF SWEET POTATO LEAVES (IPOMEA BATATAS) ON THE PERFORMANCE OF RABBIT. This study aims to examine the extent to which the use of sweet potato leaves on the performance of rabbit cattle include feed consumption, body weight gain and feed conversion. The study used 20 rabbits of New Zealand White rabbit aged 4-6 weeks with initial body weight 400-600 g / tail. The design of this study using Completely Randomized Design with 5 treatments and 4 replications with the level of sweet potato leaves in the feed that is R0: 0%, R1: 25%, R2: 50%, R3: 75%, R4: 100%. The data were tested by multiform analysis, if there is a real effect of further test using Test of Honest Significance Difference (HSD). The results showed that the provision of sweet potato leaves in rabbit fodder was significantly different (P<0.05) on rabbit performance including feed consumption, body weight gain and feed conversion`Â Keywords:Â Rabbit, Sweet Potato Leaf, Feed Consumption, Weight Gain, Feed Conversion.